2010
DOI: 10.1590/s1519-69842010000500018
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis isolates entomopathogenic for Culex quinquefasciatus (Diptera: Culicidae) and Anticarsia gemmatalis (Lepidoptera: Noctuidae)

Abstract: Samples of the Bacillus thuringiensis (Bt) were collected from soil and insects. Eight isolates were selected from rural soil, 15 from urban soil and 11 from insects. These were evaluated for entomopathogenicity against larvae of Anticarsia gemmatalis and Culex quinquefasciatus. The pathogenicity tests showed that a higher percentage of isolates were active against A. gemmatalis (60%) compared to C. quinquefasciatus (31%). Probit analysis (LC 50 ) indicated that against A. gemmatalis four of the isolates prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
(47 reference statements)
0
8
0
2
Order By: Relevance
“…Some research (Bobrowski et al, 2001;Silva et al, 2004;Monnerat et al, 2007;Silva-Werneck and Ellar, 2008;Gobatto et al, 2010) has shown the possibility of finding B. thuringiensis native isolates with toxicity to A. gemmatalis. The bioassays screening results with new B. thuringiensis isolates are useful for local and regional insect pest management.…”
Section: Discussionmentioning
confidence: 99%
“…Some research (Bobrowski et al, 2001;Silva et al, 2004;Monnerat et al, 2007;Silva-Werneck and Ellar, 2008;Gobatto et al, 2010) has shown the possibility of finding B. thuringiensis native isolates with toxicity to A. gemmatalis. The bioassays screening results with new B. thuringiensis isolates are useful for local and regional insect pest management.…”
Section: Discussionmentioning
confidence: 99%
“…Any two relevant treatments were considered as not significantly different in their toxicity if the 95% confidence intervals of their LC 50 overlapped [39]. …”
Section: Methodsmentioning
confidence: 99%
“…Considering the diverse problems associated with the massive use of these chemicals in agriculture and in environment, the biotechnology field can contribute to the discovery and development of new alternative pest control strategies (Penman, 1994). Some natural opponents including viruses (Baculovirus anticarsia) (Braconi et al, 2014;Piubelli, Hoffmann-Campo, Moscardi, Miyakubo, & de Oliveira, 2006;Piubelli, Moscardi, & Hoffmann-Campo, 2009), entomopathogenic fungi (Bertholdo-Vargas et al, 2009), and bacteria (Fiuza, Schünemann, Pinto, & Zanettini, 2012;Gobatto et al, 2010) have been used for biological control of pest populations of A. gemmatalis; however, they are not completely effective, prompting more studies to investigate better pest management strategies for agronomical applications.…”
Section: Introductionmentioning
confidence: 99%